Spatio-temporal evolution of a Tertiary carbonate platform margin and adjacent basinal deposits - Wilson, Moyra; Chambers, J.; Manning, C.; Nas, D. (Elsevier Science BV, 2012)
The variability in low to moderate energy carbonate platform margins is poorly known from the geological record. Here, the spatial and temporal evolution of platform margin and adjacent basinal deposits is evaluated from the little known Tertiary Kedango Limestone that developed in a semi-enclosed marine embayment in SE Asia. The hypothesis here is that platform margin development will reflect regional and perhaps global influences, such as tectonics, eustasy or biotic change, rather than windward-leeward effects and storms that typically impact strongly upon open oceanic platforms.The development of the carbonate platform was determined through logging, petrography, facies evaluation, provenance and high-resolution dating studies. Eleven carbonate facies were identified from the 30 km long western margin of the > 600 m thick platform and its adjacent slope and basinal deposits. Larger benthic foraminifera and coralline algal packstones and wackestones dominated in shallow waters. During the Oligo-Miocene, coral patch reef-related floatstones, rudstones and less commonly boundstones were also present on the platform top. Perhaps surprisingly for a low energy platform there was considerable variation along the platform margin and much reworking of material into slope and basinal deposits during the Oligo-Miocene. Reworked material includes shallow water bioclasts, clasts from older siliciclastics, fresh feldspars, lithified slope and platform top carbonate clasts, some of the latter showing evidence for karstification. The western platform margin varied laterally over a few kilometres from a gently sloping unrimmed platform, to a probable bank top, with in places coral-fringed, bypass and erosional faulted escarpment margins. Eustasy may have influenced shallowing and deepening trends on the platform top, but apparently had little impact on mass wasting. Instead platform margin development was strongly impacted by tectonics (including active faulting), terrestrial runoff, together with changes in carbonate producers and local variability on the platform top.